2005
DOI: 10.1111/j.1460-2695.2005.00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture tests of microsized TiAl specimens

Abstract: A B S T R A C T γ -TiAl-based materials have the ability to provide superior creep strength, high yield strength and Young's modulus at temperatures as high as 700 • C. This has led to the consideration of γ -TiAl-based materials for use in microelectromechanical systems (MEMS) intended for application at elevated temperatures. One γ -TiAl-based material under consideration for these applications is the composition known as Alloy 7/Ti-46Al-5Nb-1W (at%). In this case, this material is tested in the as-wrought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 3 publications
1
20
0
1
Order By: Relevance
“…[16,32] the prenotch was machined straight down in the central part of the sample only, leaving two side walls that formed a precrack when bend-testing thin film samples of silicon oxide, nitride or oxynitride. Testing of small-scale beams containing FIB-premachined notches has been shown in several studies to give K c values near those found for macroscopic samples [15][16][17]26,27]; however, in many other studies, different results, ranging from values slightly to much higher [11,18,19,[21][22][23][24]30,33], or in some cases lower [20,34], than the toughness data from tests on macroscopic specimens of the same material were obtained with FIB-notched specimens.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…[16,32] the prenotch was machined straight down in the central part of the sample only, leaving two side walls that formed a precrack when bend-testing thin film samples of silicon oxide, nitride or oxynitride. Testing of small-scale beams containing FIB-premachined notches has been shown in several studies to give K c values near those found for macroscopic samples [15][16][17]26,27]; however, in many other studies, different results, ranging from values slightly to much higher [11,18,19,[21][22][23][24]30,33], or in some cases lower [20,34], than the toughness data from tests on macroscopic specimens of the same material were obtained with FIB-notched specimens.…”
Section: Introductionmentioning
confidence: 77%
“…The radii of the resulting notch roots range from a few tens to several hundreds of nanometres (e.g. [11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]). Beyond the need to produce a notch of sufficient sharpness, another difficulty with ion milling lies in producing a uniform notch depth and/or width: for this reason, in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Available online at www.sciencedirect.com The challenges in mechanical testing of very thin specimens with sub-micron flaws have constrained prior studies to thicker specimens [13,14], or specimens attached to a substrate [15,16]. Specimens thicker than a few microns fall in the plane strain category, which is established in the fracture mechanics literature.…”
Section: Introductionmentioning
confidence: 99%
“…The investigations of intermetallics for MEMS materials are, however, very limited. Halford et al (2005) performed fracture tests on microsized, lamellar-structured TiAl and revealed that the lamellar orientation at the crack tip affects their fracture behavior. For the microsized, lamellar-structured TiAl, fracture toughness values (K Q ) are 1.5-7 MPa m 1/2 and are significantly smaller than that obtained for bulk material (18 MPa m 1/2 ) (Halford 2003).…”
Section: Intermetallicsmentioning
confidence: 99%